تقويم تدبير استرواح الصدر علاجي المنشأ عند الوليد - علي, وجيه; رومية, دمر; صوان, سليم (Latakia University Journal -Medical Sciences Series, 2019)
خلفية البحث: استرواح الصدرعبارة عن تجمع للهواء بين وريقتي غشاء الجنب, تقدر نسبة حدوثه 1-2% من جميع الولدان وتترافق مع نسبة وفيات عالية.إن العلاج الحالي لاسترواح الصدرهو وضع منزح في الصدر وهذه الطريقة لديها العديد الاختلاطات المحتملة, لم يعتمد العلاج المحافظ بالبزل بالإبرة كطريقة علاجية أساسية رغم قلة الاختلاطات التي تحملها . هدف البحث: تقييم نتائج علاج الاسترواح الصدري علاجي المنشأ بشكل محافظ بالبزل بالإبرة دون اللجوء إلى أنبوب فغر الصدر وتحديد الخصائص السريرية للولدان الذين يملكون القابلية للعلاج بالبزل بالإبرة. المرضى وطرائق البحث: دراسة إستقبالية من نوع Observational Descriptive Study (Case series) تشمل جميع الولدان المقبولين في شعبة الخديج والوليد في مستشفى تشرين الجامعي في اللاذقية خلال الفترة الممتدة من2018/1– 2017/1 والذين طوروا استرواح صدر بعد اجراء علاجي وبلغ عددهم 53 مريض. تمت الدراسة بالاعتماد على صورة الصدر واجراء باستخدام البزل مع اجراء صورة صدر للمراقبة وفي حال نكس الاسترواح يتم اللجوء لفغر الصدر بواسطة منزح. النتائج: شملت عينة الدراسة 53 وليد,49 مريض على التهوية الآلية, بلغ متوسط العمر الحملي 36.9 اسبوع. وبلغ متوسط الاوزان 2924 غ. 4 حالات استرواح بعد عمل جراحي (رتق مري)حدث بنسبة 100%. 8 حالات شفاء على التهوية الآلية وكان القاسم المشترك أن PINSP > 20 وذلك بنسبة 16,32%. 41 حالة نكس على جهاز التهوية الآلية وأجري لهم فغر بوضع منزح بنسبة 83,67% منها 8 حالات كانت PINSP > 20 بنسبة. نسبة الشفاء في حال قيمة PINSP > 20 كانت 50%. نسبة الشفاء الكلية من الاسترواح الصدري باستخدام البزل بالإبرة كانت 20,75% من مجمل الحالات. الخلاصة:اعتماد البزل بالإبرة كخط علاجي أساسي في حالات الاسترواح التالية لعمل جراحي. لا مانع من إجراء البزل لدى المرضى الموضوعين على التهوية الآلية خاصة اذا كانت قيمة pinsp منخفضة. Background: Pneumothorax is a combination of air between the membranes of the pleura, estimated to occur 1-2% of all newborns and is associated with high mortality. The current treatment for pneumothorax is using a chest tube that has many potential complications.Conservative treatment of needle aspiration was not adopted as a therapeutic method despite its few complications. Objective: To evaluate the results of the treatment for iatrogenic pneumothorax conservatively by needle aspiration without resorting to a thoracic tube and to determine the clinical characteristics of the newborns who have the ability to treat by needle aspiration. Patients and Methods: A prospective study of type Observational Descriptive Study (Case series) all admitted neonatal and neonatal patients at Tishreen University Hospital in Lattakia during the period 1/2017-/1/2018 who developed pneumothorax after medical procedure were 53 patients. The study was based on a X-RAY for diagnoses and make aspiration by a needle and take X-Ray for observation and use a chest tube in recurrence. Results: The study included 53 patients 49 of them with a mechanical ventilation. The average gestational age was 36.9 weeks. The average weights were 2924 g. 4 postoperative pneumothorax (Esophageal atresia) treated successfully by average 100%. 8 cases of healing on mechanical ventilation with a common denominator was PINSP< 20 by 16,32%. 41cases of mechanical ventilation system and were discharged with a vacancy rate of 83,67%, 8 of them had PINSP< 20. The cure rate in case the value of PINSP< 20 was 50%. The total recovery rate of pneumothorax using needle aspiration was 20,75%. Conclusion: using the needle aspiration as a basic treatment line in postoperative surgical conditions. There is no objection to the administration of needle aspiration in patients who are subject to mechanical ventilation, especially if the value of pinsp is low.